1998
DOI: 10.1152/ajpregu.1998.274.5.r1300
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative capacity does not protect skeletal muscle fibers from eccentric contraction-induced injury

Abstract: Isometric electrical stimulation was delivered to rabbit dorsiflexor muscles at 10 Hz for 1 s on and 1 s off over 30 min, 5 days/wk for 3 wk to induce an increase in muscle oxidative capacity. Stimulation-trained muscles as well as untrained muscles were then subjected to a 30-min eccentric exercise bout to test whether increased oxidative capacity provided a protective effect against muscle injury. Electrical stimulation resulted in significant training of both the extensor digitorum longus (EDL) and tibialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Evans et al [12] showed that endurance training of human muscle led to less damage following eccentric contractions while data from Patel et al [28] showed that, in rat muscles, increased oxidative capacity by electrical stimulation training did not result in less injury after eccentric exercise. Furthermore, Skurvydas et al [33] stated that endurance training and slow muscle fibre type prevalence does not result in less LFF, and neither does it accelerate the recovery of muscle contraction force following maximal, intermittent stretchshortening cycle exercise.…”
Section: Possible Causes Of Lffmentioning
confidence: 99%
“…Evans et al [12] showed that endurance training of human muscle led to less damage following eccentric contractions while data from Patel et al [28] showed that, in rat muscles, increased oxidative capacity by electrical stimulation training did not result in less injury after eccentric exercise. Furthermore, Skurvydas et al [33] stated that endurance training and slow muscle fibre type prevalence does not result in less LFF, and neither does it accelerate the recovery of muscle contraction force following maximal, intermittent stretchshortening cycle exercise.…”
Section: Possible Causes Of Lffmentioning
confidence: 99%
“…Studies using humans have demonstrated that repeated, intense, unaccustomed eccentric contractions result in myofibrillar ultrastructural disturbances immediately after the activity (Friden et al 1983;Newham et al 1983), delayed onset muscle soreness (Friden et al 1981;Newham et al 1987), and long-lasting muscle fatigue (Clarkson and Newham 1995). Animal studies utilizing dynamometry techniques have been used to investigate the effect of exposure to unaccustomed eccentric contractions on mice (Faulkner et al 1981;McCully and Faulkner 1986;Warren et al 1993Warren et al , 1996, rabbits (Lieber et al 1991(Lieber et al , 1996Koh and Herzog 1998;Patel et al 1998), and rats (Hesselink et al 1996;Komulainen et al 1998;Stauber 2000a, 2001). Studies using animals have shown that there is immediate post-exposure ultrastructural disorganization (Lieber et al 1991), myofiber necrosis 1-3 days after exposure (McCully and Faulkner 1986;Lowe et al 1995;Lieber et al 1996;Hesselink et al 1996;Komulainen et al 1998), and a long-lasting force decrement (Ingalls et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[93,94]. In denervated muscles the results mimic the well-known efficacy of high frequency electrical stimulation to induce skeletal muscle hypertrophy [95], and of low frequency electrical stimulation protocol to induce endurancelike adaptations when applied 5 days/week for 3 weeks [81,96,97]. Recent evidence shows that trophism and fiber type are regulated independently through different transduction signaling pathways [98][99][100][101].…”
Section: Muscle Trophismmentioning
confidence: 62%